Dynamics of Salafiyah Islamic Boarding Schools: Enhancing Religious Identity and Fostering Independence - Rifa, Moh (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2023)
This study aims to analyze the efforts of the salaf Islamic boarding schools and their implications in strengthening identity at the Nurul Qadim Islamic boarding school, Probolinggo, East Java. This study uses a qualitative approach to the type of case study. Data collection techniques in this study used three techniques, namely: participant observation, in-depth interviews, and documentation. Data analysis was carried out using data reduction, data display, and conclusion drawing/verification. The research results show that; The efforts of the salaf Islamic boarding schools to strengthen identity at the Nurul Qadim Islamic boarding school are carried out by means of; strengthens its salafi identity, is not affected by the dynamics of the times, has its own curriculum, builds the image of the institution, and is not old-fashioned. The implications of strengthening the religion and independence of Islamic boarding schools for the identity of the Nurul Qadim Islamic boarding school are curriculum reconstruction, strengthening the concept of Islamic values, strengthening partnerships and strengthening work ethics.